The Role of Artificial Intelligence in Improving Efficiency of the Legal System - Untung Saritomo; Ahmad Redi (Jurnal Indonesia Sosial Teknologi, 2025)
Artificial intelligence (AI) has become one of the most significant technological innovations in various sectors, including the legal system. With its ability to analyze big data and detect complex patterns, AI has the potential to improve the efficiency and effectiveness of law enforcement. This article will discuss the role of AI in improving the efficiency of the legal system as well as the challenges faced in its implementation. This article aims to explore how AI technology can be integrated into legal practice to speed up the decision-making process, reduce operational costs, and improve the accessibility of legal services. The writing of this article uses a qualitative approach, with data collection methods through desk study, the legal sources used are primary, secondary and tertiary legal sources. The results show that artificial intelligence has an important role to play in improving the efficiency of the legal system through big data analysis, automation of legal processes, and offense detection. However, despite its significant benefits, ethical and regulatory challenges related to the use of AI in the legal system also need to be addressed. Issues such as data privacy and algorithmic bias must be addressed so that the implementation of these technologies does not disadvantage certain parties. With the right strategy and collaboration between the government and the private sector, AI can be an innovative tool to improve the legal ecosystem in the future. Overall, artificial intelligence has great potential to revolutionize the legal system by improving operational efficiency and service accessibility. Further research is needed to fully understand the long-term impact of integrating this technology in legal practice.